Letter (copy) - Citrine, Walter, 1887-1983
001-0086-001 Secretary's WMC/FEM/MMC/307 26th February 1945. Mr. Amaro del Rosal, General Workers'Union of Spain, 22.Inverness Terrace,W.2 Dear Mr.del Rosal, I have just received your letter of the 25th February, stating that the Executive Committee of the General Workers'union of Spain In Mexico has mandated you on a special mission to me. I regret it is physically impossible for me to see you this week owing to a series of meetings of the General Council and sub-committees. However, I should be very pleased if you could come here and see Mr.Bell the Secretary of our International Department. I have the fullest confidence in him and I am sure he could give any advice necessary. I think this is the best way if the matter is urgent to you. Yours sincerely, General Secretary. 292/946/1/86